Relationship between sleep abnormalities and hypothyroidism: results from the National Health and Nutrition Examination Survey 2007-2012 - Yan Ding; Yulan Peng; Jing Zhang; Xu Huang; Xueqin Pan; Chunquan Zhang (BMC, 2024)
Abstract Background Studies have emphasised the adverse effects of poor sleep on human health, however, the correlation between sleep abnormalities and hypothyroidism remains unclear. This study evaluated whether sleep abnormalities may be related to increased prevalence of hypothyroidism in general US adults. Methods: In total, 9016 adults who participated in the National Health and Nutrition Examination Survey from 2007 to 2012 were analysed. A standardised questionnaire was used to collect data regarding sleep duration, self-reported trouble sleeping and sleep disorders. Values were assigned to the three aforementioned sleep factors, resulting in an overall sleep score of 0-3. The sleep patterns were divided into healthy sleep pattern (overall sleep score = 3), intermediate sleep pattern (overall sleep score = 2) and poor sleep pattern (overall sleep score = 0 or 1) according to a former study. Hypothyroidism was defined as thyroid-stimulating hormone (TSH) levels > 5.6 mIU/mL or the need to take thyroid hormones. Multivariable logistic regression analysis was performed to assess the relationship between sleep abnormalities and hypothyroidism. Results: The overall prevalence of hypothyroidism was 8.0% among the 9016 participants. Self-reported trouble sleeping (odds ratio [OR] = 1.38, 95% CI: 1.14-1.68, p = 0.001) and sleep disorders (OR = 1.40, 95% CI: 1.06-1.86, p = 0.0196) were associated with increased prevalence of hypothyroidism. Neither short sleep duration (OR = 0.99, 95% CI: 0.82-1.19) nor long sleep duration (OR = 0.98, 95% CI: 0.61-1.58) was significantly associated with hypothyroidism. Moreover, poor sleep pattern was significantly associated with increased prevalence of hypothyroidism (OR = 1.30, 95% CI: 1.03-1.66, p = 0.0301). Conclusions: Both trouble sleeping and sleep disorders were associated with increased prevalence of hypothyroidism.